THE IMPACT OF SOCIAL MEDIA ON STUDENTS (Ustozlar uchun, 2025)
This paper explores how social media influences students’ academic outcomes. Platforms such as Instagram, TikTok, Facebook, and Telegram are commonly used by learners for communication, entertainment, and educational purposes. While these networks can enrich education by offering access to information and fostering collaborative learning, excessive engagement may undermine concentration, time management, and academic success. The study discusses both the advantages and drawbacks of social media use and emphasizes the need for balanced and responsible engagement.